Способ плазменно-порошковой наплавки модулированным током - Дедюх Р. И. Ростислав Иванович; Азаров Н. А. Николай Антонович; Звирь Ю. В.; Верник Л. А.; Чернов М. Г.; Щуплецов Е. А.; Тагиров М. М.
опубл. 07.05.90